Geothermal Map of Perú - Vargas Rodríguez, Víctor (2010)
The Andes Cordillera resulted from the interaction of the Nazca Plate and the South American Plate. The subduction process occurring between both plates has controlled all geological evolution of such territory since Mesozoic to present time. In this context, magmatic and tectonic processes have allowed the development of geothermal environments with great resources to be evaluated and subsequently developed making a sustainable exploitation of them. In consequence, Perú has a vast geothermal potential with many manifestations at the surface as hot springs, geysers, fumaroles, steam, etc., all over the country. The first geothermal studies began in the 70's with the first inventory of mineral and thermal springs. In this work the Geothermal Map of Perú is presented in order to geographically define the zones of the country where geothermal resources are located. Currently six important geothermic regions have been identified: Cajamarca – La Libertad; Callejón de Huaylas; Churín; Central; Eje Volcánico Sur and Cuzco – Puno. From the analysis of bibliographic information and field studies, it was concluded that in both, in northern and central Peru high temperature manifestations are the result of the geothermal gradient, in which the water flows across deep faults. Whereas in the southern part of the country the geothermal manifestations are related to active volcanism. In this zone the hot springs are of mixed origin, composed by meteoric and volcanic water. Until now, most of the studies to characterize geothermal resources in Perú have been focused on the Eje Volcánico Sur zone, located in the southern part of the country where several zones with different geothermal importance have been recognized. Group A: High importance: Tutupaca, Calacoa, Maure, Laguna Salinas, Chachani and Chivay. Group B: Medium importance: Puquio, Parinacochas and Orcopampa. Group C: Low importance: Catahuasi, Coropuna, Caylloma and Mazo Cruz. Finally, it is important to mention that the present status of investigation of geothermal resources in Perú is in the exploration stage. At this point the geothermal map developed constitutes a tool to follow investigations that contribute in the development of this environmentally friendly resource, for electric power generation and direct uses.